Porous polyurethane foams based on recycled poly(ethylene terephthalate) for oil sorption. Issue 1 (6th September 2012) - Atta, Ayman M.; Brostow, Witold; Datashvili, Tea; El‐Ghazawy, Rasha A.; Lobland, Haley E. Hagg; Hasan, Abdul‐Raheim M.; Perez, Jose M.
Abstract: In using recycled poly(ethylene terephthalate) (PET) as a petroleum sorbent we tried to achieve two important objectives simultaneously. PET waste was glycolized using trimethylolpropane (TMp) or pentaerytheritol (PEr) to produce suitable polyol oligomers for polyurethane (PU) foams. The glycolysis was carried out in the presence of manganese acetate as a catalyst under normal pressure in m ‐cresol at 220 °C. Producing polyols, PEr degraded PET into lower molecular weights than TMp. So prepared oligomers were reacted with 2, 4‐toluene diisocyanate providing several types of PU foam. The effect of various variables (polyol reactivity, water content, type of catalyst, isocyanate amount and surfactant) on the foam structure and properties were analyzed. Porosity of the PU foams was examined using environmental scanning electron microscopy. Foams based on glycolized TMp contain small uniform cells whereas other foams form less uniform cells with varying sizes including closed cells. Dynamic mechanical analysis gives much lower storage moduli for TMp‐based PUs that for those based on PEr, an effect of dangling ethylene chains in the former case. The glass transition temperatures T g are higher when PEr rather than TMp is used. Our PU foams show good sorption properties and sufficient reusability. Copyright © 2012 Society of Chemical Industry Abstract : We have synthesized foams that absorb petroleum or toluene much more than their original weight. Subsequent desorption leaves inside only some 2 % of the liquid absorbed; thus, the foams are usable as absorbers multiple times.